Implementasi Metode AIDA dalam Penulisan Naskah Video Iklan Apartemen Vasaka Solterra - Indah Ratna Dewi; Alfi Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study discusses the implementation of the AIDA (Attention, Interest, Desire, Action) writing technique in the scriptwriting process of advertisement videos for Vasaka Solterra apartments. The study was conducted based on the development of digital media and the increasing use of short video content as a marketing communication medium in the property sector. The purpose of this study is to analyze the application of the AIDA technique in advertising scriptwriting in order to produce persuasive and systematic messages. This study employed a descriptive qualitative approach through observation, active participation, and literature review. The results show that the implementation of the AIDA technique was able to structure the message flow systematically, starting from attracting audience attention, generating interest, creating desire, and encouraging action through a call to action. In educational advertisements, the AIDA technique successfully increased audience awareness of common mistakes in purchasing apartments, while in promotional advertisements, the technique strengthened the connection between lifestyle, audience needs, and property offerings. This study concludes that the AIDA technique can support the quality of short-duration property advertisement video content through persuasive, relevant messages that are aligned with current digital audience preferences, thereby strengthening the quality of marketing communication on social media.